Faster IgG4 Depletion Kinetics Observed for Anti-Desmoglein 3 Autoantibodies Following Rituximab Treatment in Patients with Pemphigus Vulgaris - Katharina Boch; Ewan A. Langan; Nina van Beek; Khalaf Kridin; Enno Schmidt; Detlef Zillikens; Ralf J. Ludwig; Christoph M. Hammers; Katja Bieber (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)